The Results of the Study of the Compactions of the Bottom of the Furrow in Plowing by Plug Corpusies as well as Tractor Wheels - U.I.Khasanov; M.M.Makhmudova; A.A.Savriddinov; K.S.Sobirov; SH.T.Safarov (Zien Journals, 2022)
In this article, the physical and mechanical properties of the soil during plowing, that is, hardness, density, In order to study the humidity, the results of the researches are presented
Keywords: plug,; corpus,; knife; soil-deepener; soil moisture; soil hardness